Drawing the Reasons of Constructed Space. Eighteenth-Century Neapolitan Open Staircases (diségno, 2017)
Eighteenth-century Neapolitan open staircases are an urban and architectural event of unusual wonder. Created by the architect Ferdinando Sanfelice, they are masterful examples of a new formal and structural experiment. In this article, the origins of the Sanfelician staircases are discussed. They were chosen due to their particular urban, spatial and constructive value and have been the subject of an architectural and environmental survey campaign carried out through a direct method coordinated by the author. The origins of the Sanfelician staircases will be studied, highlighting the geometric-configurative arrays of their two main models, i.e. the ‘falcon wings’ and the ‘cantilevered.’ Due to its important architectural function, the staircase of a project is as old as the architecture itself. However, it is in the Baroque period that we experience forms that restore the staircase of a project as a space-time configuration representative of the architecture, along with not only the monumental but also the imaginative dimension. Eighteenth-century Neapolitan open staircases originated in the 1400s and are architectural organisms characterized by particular space-perception relationships. The diagrams compare (for the first time and to the same scale of representation) the staircases designed by Sanfelice in Naples. These issues have been dealt with in an architectural survey campaign of several staircases in Naples (2014-2017), where the spatial layout refers to the Sanfelician models discussed here; the results of the comparative analyses, respectively between the staircases of the Sanfelice, Maciocco, Palmarice and Persico palaces are presented here.
Keywords: rilievo architettonico, geometria dei modelli, Ferdinando Sanfelice.